2021
DOI: 10.17305/bjbms.2021.6340
|View full text |Cite
|
Sign up to set email alerts
|

Sustained seroprevalence of SARS-CoV-2 antibodies one year after infection: one of the first COVID-19 cluster cases in Bosnia and Herzegovina

Abstract: SARS-CoV-2 (severe acute respiratory syndrome coronavirus type 2) is a novel virus that has been identified as a causal agent of COVID-19,  an emergent infectious disease which brought about a new pandemic in the twenty-first century. The immune responses and clinical features of individuals infected with SARS-CoV-2 have not yet been fully described. Thus, in this study, we compare the seroprevalence and define the correlation between symptoms and serological results in the first COVID-19 cluster in the city o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Symptoms of high fever and headache could be possible indicators of a better immune response as they have shown correlation with IgG levels. The study has also shown a significant increase in antibody titers of vaccinated participants one year after infection which could possibly point to better protection against reinfection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of high fever and headache could be possible indicators of a better immune response as they have shown correlation with IgG levels. The study has also shown a significant increase in antibody titers of vaccinated participants one year after infection which could possibly point to better protection against reinfection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protective behavior is crucial to managing a pandemic, and effective immunization could bear the most promise for resolving the health issue of COVID-19 pandemic [ 14 , 23 ]. During 2020, several vaccines were being developed in multiple countries, and by the end of the year, results of the phase 3 trial had been published which resulted in the approval of the vaccines against COVID-19 [ 15 - 17 , 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the large majority of participants had COVID-19 or had been vaccinated with 2 doses well before enrolment in the study, we can assume that their immunity waned over time. Furthermore, our previous study demonstrated sustained titers of SARS-CoV-2 IgG antibodies over one year of infection, implicating that specific neutralizing IgGs are crucial for control of virus spreading rather than sustained IgG titers [13].…”
Section: Discussionmentioning
confidence: 87%
“…Plasma cells produce antibodies against infection by viral antigen [37] . In a subject with SARS-CoV-2 disease, B lymphocytes produce IgM and IgG antibodies against viral proteins S, E, M, and N [38] . Significant and uncontrolled release of proinflammatory cytokines in patients with SARS-CoV-2 infection causes cytokine storm syndrome and ARDS [39] .…”
Section: Introductionmentioning
confidence: 99%
“…Viruses must evade the immune system to cause infection/illness in humans. The SARS-CoV-2 virus suppresses the production of interferon (IFN type I and IFN type III) glycoprotein, which stimulates innate immune cells in host cells to fight against microbes or harmful cells that enter the body to prevent recognition by receptors on host cells [38] . Interferon stimulates innate immune cells against viral infection by activating type I and type III IFNs, thus preventing viral protein synthesis and limiting virus infection by generating immune responses [42] .…”
Section: Introductionmentioning
confidence: 99%